Supporting diversity and inclusion with story authentic folktales and discussion guides - Ford, Lyn 1951-; Norfolk, Sherry 1952- (Santa Barbara, California Libraries Unlimited, an imprint of ABC-CLIO, LLC, 2020)
"This treasury of authentic world folktales helps develop cultural understanding."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Storytelling; Folklore -- Study and teaching (Elementary); Multicultural education